Engineering mathematics for marine applications - Korde, Umesh A.; Ertekin, Rifat Cengiz (Cambridge ; New York, NY : Cambridge University Press, 2023)
Gaining expertise in marine floating systems typically requires access to multiple resources to obtain the knowledge required, but this book fills the long-felt need for a single cohesive source that brings together the mathematical methods and dynamic analysis techniques required for a meaningful analysis, primarily, of large and small bodies in oceans. You will be introduced to fundamentals such as vector calculus, Fourier analysis, and ordinary and partial differential equations. Then you'll be taken through dimensional analysis of marine systems, viscous and inviscid flow around structures surface waves, and floating bodies in waves. Real-life applications are discussed and end of chapter problems help ensure full understanding. Students and practicing engineers will find this an invaluable resource for developing problem solving and design skills in a challenging ocean environment through the use of engineering mathematics.
Vector calculus-I -- Vector calculus-II -- Complex variables -- Fourier analysis -- Ordinary differential equations-I -- Ordinary differential equations-II -- Partial differential equations-I -- Partial differential equations-II -- Dimensional analysis -- Viscous-fluid flow -- Ideal-fluid flow -- Water waves -- Wave diffraction and wave loads -- Prescribed body motions and floating bodies -- Irregular-sea analysis -- Introduction to analytical dynamics.
Title from publisher's bibliographic system (viewed on 11 May 2023).
Keywords: Ocean engineering -- Mathematical models; Engineering mathematics